2021
DOI: 10.1002/essoar.10507525.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping the thermal structure of southern Africa from Curie depth estimates based on wavelet analysis of magnetic data with uncertainties

Abstract: Estimating the spatial variations in the temperature within the Earth is important to constrain the thermal structure and the rheology of the lithosphere (Audet & Gosselin, 2019). Curie depth estimates, which correspond to the depth where crustal rocks reach their Curie temperature (∼580 • C for magnetite; Dunlop & Özdemir, 2001) give independent temperature constraints over an area where magnetic anomaly data are available. Above the Curie temperature, the ability of rocks to preserve ferromagnetic magnetism

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…A physics-based geothermal heat flow map of Southern Africa obtained from a single observable (namely, the Curie depth as inverted from magnetic anomaly information) has been presented in Sobh et al (2021). It is notable that the multi-observable based model AFQ presented here predicts lower heat flow along South African cratonic blocks (KC and ZC), while the model by Sobh et al…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…A physics-based geothermal heat flow map of Southern Africa obtained from a single observable (namely, the Curie depth as inverted from magnetic anomaly information) has been presented in Sobh et al (2021). It is notable that the multi-observable based model AFQ presented here predicts lower heat flow along South African cratonic blocks (KC and ZC), while the model by Sobh et al…”
Section: Discussionmentioning
confidence: 79%
“…Studies by He et al (2022); Shahdi et al (2021) compared several machine learning (ML) methods for geothermal heat flow modeling at regional scales and indicated that these methods can perform as good as, and sometimes better than, physics-based models. Physics-based models (such as, e.g., Lösing et al (2020); Sobh et al (2021)) often require various simplifications and are feasible only for few geophysical observables. Thus, if one wants to include several different geophysical and geological observables for the prediction of GHF, as seems necessary for continental scale models, purely physics-based models become unfeasible.…”
Section: Introductionmentioning
confidence: 99%
“…CPDs for the mid‐Norwegian margin in the area of the Trøndelag Platform and Vøring Basin are reported to range from 18 to 20 km at the coast, around 12 km at the ocean continent transition zone and beneath the oceanic plate to be in the order of about 9 km (Ebbing et al., 2009) CPDs beneath the British Isles are reported to range from 15 to 45 km (Mather & Fullea, 2019). CPDs in southern Africa are reported to range from 8 to 15 km along the Okavango Rift zone in Botswana and up to 50 km in the Kaapvaal Craton (Sobh et al., 2021). Curie depths substantially shallower are reported for the West Antarctic Rift system, reaching depths shallower than 10 km and up to extreme values of 4.8 km (Dziadek et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Adding an unconstrained fractal parameter adds complexity which is difficult to tie down since different geological terrains would require different β values. Fixing β to a constant value as previous studies have done, for example, (Sobh et al., 2021) will not provide an advantage over a random magnetization model. A recent study illustrated the difficulty in estimating reliable β values and highlights the possibility that β is only valid in a limited bandwidth (Szwillus et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Although the isopycnic hypothesis might not be valid for the Kaapvaal craton (Schutt & Lesher, 2010), our obtained results fit well to previous findings. It is evident from several studies (e.g., Brey & Shu, 2018; Griffin, O’Reilly, Natapov, & Ryan, 2003; Lazarov et al., 2009; Sobh et al., 2021; Weiss et al., 2021) that the present‐day Kaapvaal craton is the result of several depletion episodes followed by a range of metasomatic refertilizations. Thus, values of Mg# up to 90.5 at 100 km depth probably mark remnants of the depleted cratonic root (Figure 9 EE′).…”
Section: Discussionmentioning
confidence: 99%